AB0269 Cardiovascular Risk Assessment in Persons with Autoimmune Rheumatic Disease: A Pilot Study of Non-Invasive Arterial Health Testing. (15th July 2016) - Scanlon, E.M.; Mankad, R.; Crowson, C.S.; Kullo, I.J.; Mulvagh, S.L.; Matteson, E.L.; Kvrgic, Z.; Davis, J.M.
Abstract : Background: Persons with rheumatoid arthritis (RA) have increased mortality attributable to atherosclerotic cardiovascular disease (ASCVD) events. While a heightened risk of ASCVD events exists in patients with RA, we have yet to uncover an accurate method for estimating that risk. It is unknown how the current state of disease activity affects arterial function in early subclinical ASCVD. Objectives: Our goal is to determine the effect of the current state of inflammatory disease activity, as measured by the Simplified Disease Activity Index (SDAI) and Health Assessment Questionnaire (HAQ) score, on arterial health in patients with RA, using an innovative non-invasive testing package developed at Mayo Clinic in Rochester, Minnesota. Methods: We recruited a cohort of 50 patients with RA as defined by the 2010 American College of Rheumatology/European League Against Rheumatism classification criteria, and conducted non-invasive arterial health testing on the same day as a rheumatologic assessment of clinical disease activity, which was classified in terms of tender/swollen joint counts, SDAI score and HAQ score. This arterial health testing package includes measurements of endothelial function (brachial artery reactivity testing, BART), arterial stiffness (pulse wave velocity, PWV), and early atherosclerosis (carotid intima-media thickness, CIMT, and carotid plaque presence). Statistical analysis was performed with Spearman Correlation Coefficients between the rheumatologic disease activity scores and arterial health testing parameters. Results: Our 50 patients had mean (SD) disease duration of 7.0 (±4.0) years, mean age of 57.2 years, and 38 (76%) were female. The average disease activity was moderate, with mean (SD) SDAI of 21.4 (±17.4); 27 patients had either moderate or high disease activity by SDAI. A statistically significant correlation emerged between the SDAI score and the following measures: corrected aortic augmentation index (r=0.35, p=0.012); and the CIMT of the right common carotid artery (r=0.28, p=0.048). The correlation between SDAI and aortic PWV was borderline (r=0.26, p=0.067). The HAQ score correlated significantly with the corrected aortic augmentation index (r=0.33, p=0.019), but not with PWV or CIMT measures of right and left common carotid artery. Conclusions: We identified significant correlations between SDAI, and measures of arterial stiffness (i.e., corrected aortic augmentation index), and subclinical atherosclerosis (i.e., CIMT). The HAQ score significantly correlated with the corrected aortic augmentation index. This study suggests that the current state of disease activity in RA does significantly influence several measures of arterial health using this testing package. Disclosure of Interest: None declared